Studi Literatur Tentang Peran Guru Dalam Perkembangan Peserta Didik - Mohammad Riefyal Moulana; Ichsan; Fatur Rahman (Advances In Education Journal, 2025)
One of the problems with current education is the inadequate role of teachers in developing all students, especially in the digital era. A literature review on students' cognitive, social-emotional, character and learning motivation is used to investigate the strategic role of teachers. To do so, a literature review was conducted by finding and analyzing relevant previous research findings. The results show that teachers function as facilitators, motivators, mentors and role models in creating effective and rewarding learning. Teachers also face issues with digital literacy, students' motivation to learn, and character building. This study enhances our understanding of the importance of improving teacher skills. The result is that the overall success of student development is greatly influenced by improved teacher professionalism and collaboration with parents.